IDENTIFICATION OF OLIGOSTILBENES FROM Dipterocarpus semivestitus THROUGH DEREPLICATION TECHNIQUE (Jurnal Teknologi (Sciences & Engineering), 2015)
Three oligostilbenes have been identified in stems extract of Dipterocarpus semivestitus through dereplication strategy. The stems extract was injected to liquid chromatography tandem mass spectroscopy. Two tetramer, hopeaphenol and hemsleyanol D, were identified by comparing their mass fragmentation patterns with in-house library. A trimer, a-viniferin was isolated by various separation techniques and its structure was confirmed by NMR analyses and comparison with published data.
Keywords: Dipterocarpaceae; Dipterocarpus semivestitus; resveratrol oligomers; tandem MS; dereplication